Effect of Carbon Dioxide on the Reactivity of the Oxidation of Boron Particles. Issue 4 (5th February 2014) - Li, Heping; Ao, Wen; Wang, Yang; Zhou, Hua; Liu, Jianzhong; Zhou, Junhu
Abstract Carbon dioxide produced in the primary combustion of propellants apparently affects the combustion of boron. In this study, the thermodynamic and kinetic properties of the combustion of boron particles in a CO2 environment (solely or as a mixture with other gases) were investigated using thermogravimetric analyses. For the combustion of boron in an atmosphere containing 10 % oxygen, in addition to a large initial weight gain, a second increase in weight was observed when the temperature reached 1150 °C. However, when the combustion was carried out in pure CO2 atmosphere, the sample lost weight at temperatures above 1300 °C. The above results indicated that the layer of boron oxide covering the boron particles had a significant effect on the combustion process. With a limiting concentration of O2 (10 %), the initial temperature and effective activation energy slightly decreased as the content of CO2 increased from 0 to 30 %. However, a further increase in the CO2 content (50 %) increased the effective activation energy, indicating the inhibitory effects of CO2 at higher concentrations. Furthermore, the weight and the rate of weight gain gradually increased with increasing CO2 content. This behavior was attributed to the improvement in the diffusion of the oxidant. This study conclusively revealed that the inclusion of an optimal level of CO2 in a reaction environment containing O2 facilitated the combustion of boron particles.